2021
DOI: 10.1111/1753-6405.13088
|View full text |Cite
|
Sign up to set email alerts
|

The Collaboration for Increasing Influenza Vaccination in Children (CIIVIC): a meeting report

Abstract: Table 1: Interventions identified and evaluated by attendees for improving influenza vaccination in children with comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Apart from special risk or travel vaccines, the seasonal influenza vaccine is the only recommended but not funded vaccine that primary school children 5 to 11 years may receive. Uptake of influenza vaccine in this age group remains low (29.7% in children 5 to <10 years compared to 45.2% in children 6 months to <5 years in 2020), especially for children with no medical comorbidities [3] , [4] . In addition, several local and international studies had suggested that many parents of children 5 to 11 years were reluctant to have their child vaccinated against COVID-19 [5] , [6] , [7] , [8] , [9] , [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from special risk or travel vaccines, the seasonal influenza vaccine is the only recommended but not funded vaccine that primary school children 5 to 11 years may receive. Uptake of influenza vaccine in this age group remains low (29.7% in children 5 to <10 years compared to 45.2% in children 6 months to <5 years in 2020), especially for children with no medical comorbidities [3] , [4] . In addition, several local and international studies had suggested that many parents of children 5 to 11 years were reluctant to have their child vaccinated against COVID-19 [5] , [6] , [7] , [8] , [9] , [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%